2008
DOI: 10.1111/j.1365-2621.2007.01590.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hot air‐drying and freeze‐drying on the physicochemical properties and antioxidant activities of pumpkin (Cucurbita moschata Duch.) flours

Abstract: Freeze-drying and hot air-drying were applied in the preparation of pumpkin flours to investigate the effects of drying methods on the antioxidant activities and physicochemical properties. The antioxidant activities of methanol extracts from pumpkin flours were studied in terms of total antioxidant activity, reducing power, free radical scavenging, superoxide anion radical scavenging and metal chelating activities. Hot air-dried pumpkin flour showed stronger antioxidant activities than freeze-dried flour. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
157
1
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(195 citation statements)
references
References 32 publications
23
157
1
14
Order By: Relevance
“…This increase in the solubility can be attributed to the increased degradation of starch during hot air drying. Similar results were obtained by 16 in the drying of pumpkin. The solubility of the samples was found to vary significantly.…”
Section: Determination Of Solubilitysupporting
confidence: 78%
“…This increase in the solubility can be attributed to the increased degradation of starch during hot air drying. Similar results were obtained by 16 in the drying of pumpkin. The solubility of the samples was found to vary significantly.…”
Section: Determination Of Solubilitysupporting
confidence: 78%
“…Although non-thermal freeze drying is often considered to be the best drying method for preserving heat sensitive compounds, the results show that higher total phenolic content and antioxidant capacity were obtained with thermal methods for date fruit. Que et al (2008) reported that hot air dried pumpkin flour contained higher total phenolic content and antioxidant activity than freeze dried sample, possibly due to production of Maillard products. The increase in antioxidant capacity as a result of drying might be caused by the formation of new antioxidant compounds (Albanese et al, 2013).…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…cause more phenolics to be extracted. In addition, the increase in phenolic content could be explained by the formation of Maillard reaction products, which would cause new phenolic compounds to form from precursors during thermal treatments (Que et al, 2008;Sultana et al, 2012). The highest phenolic content in microwave-dried dates might be because of the high temperatures reached in the during microwave treatment, which could cause greater cell disruption and lead to rupturing that releases phenolic compounds.…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…This could be due to the conditions of the drying process, which may influence the antioxidant activity and TPC. Other studies have reported that the drying method, temperature and time of the treatment, type of extraction, and interactions among the different antioxidant reactions could be responsible for the difference in responses of the phenolic compounds to the Folin-Ciocalteu method (Balasundram et al 2006;Que et al 2008;Vega-Gávez et al 2009). …”
Section: Total Phenolic Content (Tpc)mentioning
confidence: 99%